TIDAL ASYMMETRY IN MANGROVE FOREST - CASE STUDY IN SOUTHERN VIETNAM - Dung, Tran Xuan; Phuoc, Vo Luong Hong (Vietnam Journal of Marine Science and Technology, 2019)
The study aims to analyse the tidal asymmetry in mangrove forest by using the numerical modelling and the measured data in two mangrove forest areas: Can Gio (Ho Chi Minh city) and Cu Lao Dung (Soc Trang province). The results of 2D model in the mangrove forest show that there is the asymmetry in current velocity: Two velocity peaks exist at flood tide and two at ebb tide. The current velocity is the sum of the tidal flows from the channel and from the tidal exchange between the creek and the swamp. The calculated velocity depends strongly on drag force, which is due to the mangrove vegetation. Furthermore, the results from analysing the measured data in February 2012 in Can Gio, Ho Chi Minh city and in Sept–October 2014 in Cu Lao Dung (Soc Trang) also prove the existence of the tidal asymmetry: The current velocity in the mangrove at flood tide is more dominant than velocity at ebb tide. The water level also has the asymmetry, changes in the tidal cycles but does not get so dominant as the velocity does.